Folate Metabolism in Hepatocellular Carcinoma. What Do We Know So Far? - Jaqueline Quevedo-Ocampo MSc; Alejandro Escobedo-Calvario MSc; Verónica Souza-Arroyo PhD; Roxana U. Miranda-Labra PhD; Leticia Bucio-Ortiz PhD; María C. Gutiérrez-Ruiz PhD; Lisette Chávez-Rodríguez PhD; Luis E. Gomez-Quiroz PhD (Technology in Cancer Research & Treatment, 2022)
Cancer cells are characterized by accelerated proliferation and an outstanding adaptation of their metabolic pathways to meet energy demands. The folate cycle, also known as folate metabolism or one-carbon metabolism, through enzymatic interconversions, provides metabolites necessary for nucleotide synthesis, methylation, and reduction power, helping to maintain the high rate of proliferation; therefore, the study of this metabolic pathway is of great importance in the study of cancer. Moreover, multiple enzymes involved in this cycle have been implicated in different types of cancer, corroborating the cell's adaptations under this pathology. During the last decade, nonalcoholic fatty liver disease has emerged as the leading etiology related to the rise in the incidence and deaths of hepatocellular carcinoma. Specifically, cholesterol accumulation has been a determinant promoter of tumor formation, with solid evidence that an enriched-cholesterol diet plays a crucial role in accelerating the development of an aggressive subtype of hepatocellular carcinoma compared to other models. In this review, we will discuss the most recent findings to understand the contribution of folate metabolism to cancer cells and tumor microenvironment while creating a link between the dynamics given by cholesterol and methylenetetrahydrofolate dehydrogenase 1-like, a key enzyme of the cycle located in the mitochondrial compartment.